Assessment of possible small fiber Neuropathy in early-stage vitamin B12 deficiency using electrophysiological methods - Issi, Elif Simin (Arquivos de Neuro-Psiquiatria, 2025)
Small fiber neuropathy (SFN) affects thinly myelinated and unmyelinated fibers, often presenting with subtle clinical signs that are undetectable in routine nerve conduction studies. Vitamin B12 deficiency is a known risk factor for SFN, yet early-stage cases frequently remain undiagnosed. Sympathetic skin response (SSR) and cutaneous silent period (CSP) are noninvasive electrophysiological techniques used to assess autonomic and somatic small fiber function.The present study aimed to evaluate the diagnostic utility of SSR and CSP in detecting possible subclinical small-fiber neuropathy (pSFN) in individuals with early-stage vitamin B12 deficiency.The present observational study included 28 patients with vitamin B12 deficiency who had nonspecific complaints, Douleur Neuropathique en 4 Questions (DN4) scores < 4, and normal nerve conduction studies, along with 25 healthy controls. Electrophysiological testing involved SSR recordings from all extremities and CSP measurements from the right median and sural nerves.In the patient group, Median Nerve Cutaneous Silent Period (MN-CSP) and Tibialis Anterior -Sural Cutaneous Silent Period (TA-sural CSP) durations were significantly shorter, while termination and onset latencies were prolonged compared with controls. MN-CSP and TA-sural CSP durations demonstrated high diagnostic accuracy. Sympathetic skin response latencies were significantly prolonged in both hands and feet, indicating autonomic dysfunction. No significant differences were observed in SSR amplitudes.Sympathetic skin response and CSP are valuable tools for detecting possible subclinical SFN in vitamin B12 deficiency. Sympathetic skin response effectively identified autonomic dysfunction, while CSP provided additional diagnostic value for somatic small fiber impairment. Combining SSR and CSP may enhance early detection of pSFN in vitamin B12 deficiency and allow timely intervention.
Keywords: Vitamin B 12 Deficiency; Small Fiber Neuropathy; Galvanic Skin Response; Reflex, Abnormal; Electrodiagnosis